Penggunaan Model Pembelajaran Explicit Instruction Dengan Trainer PLC Untuk Meningkatkan Prestasi Belajar Merakit Sistem PLC - Suroto Suroto (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
The purpose of the research was to implement the Explicit Instruction Learning Model using trainer PLC media to improve the students’ learning achievement and motivation in assembling PLC system subject. The research methodology used classroom action research with XII TOI students of SMK Negeri 2 Depok as the sample. The research instruments used were formative tests and practice job sheets. The result of research showed that the average formative test in cycle I was 76,10 ; in cycle II was 80,32 and in cycle III was 83,77. Based on the findings, it means that the students ‘scores were higher than the provided minimum requirement score after using the Explicit Instruction Model using trainer PLC media in cycle I,II and III. The students’ learning motivation in cycle I, II and III were 67, 82 ,and 85 respectively. It can be concluded that the students’ learning motivation was improving from (≤ 75 ) to ( ≥ 75 ) at the second and third cycles.